2006
DOI: 10.1121/1.2180210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of masker type on native and non-native consonant perception in noise

Abstract: Spoken communication in a non-native language is especially difficult in the presence of noise. This study compared English and Spanish listeners' perceptions of English intervocalic consonants as a function of masker type. Three maskers (stationary noise, multitalker babble, and competing speech) provided varying amounts of energetic and informational masking. Competing English and Spanish speech maskers were used to examine the effect of masker language. Non-native performance fell short of that of native li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
201
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(231 citation statements)
references
References 30 publications
25
201
5
Order By: Relevance
“…Van Engen and Bradlow (2007) recently showed that the language used as masker can affect the intelligibility of target speech: sentence recognition is poorer when the background babble is the same language as the one of the target speech compared to when they are different (see also Garcia Lecumberri andCooke, 2006 andRhebergen et al, 2005 for similar findings). Although these results provide evidence for informational masking in the form of linguistic interference, the exact linguistic features that contribute to this effect are still unspecified.…”
Section: Introductionmentioning
confidence: 53%
“…Van Engen and Bradlow (2007) recently showed that the language used as masker can affect the intelligibility of target speech: sentence recognition is poorer when the background babble is the same language as the one of the target speech compared to when they are different (see also Garcia Lecumberri andCooke, 2006 andRhebergen et al, 2005 for similar findings). Although these results provide evidence for informational masking in the form of linguistic interference, the exact linguistic features that contribute to this effect are still unspecified.…”
Section: Introductionmentioning
confidence: 53%
“…These results indicate that even very skilled non-native listeners may have difficulty understanding speech in the presence of reverberation. (Bradlow & Bent, 2002;Cooke, Lecumberri, & Barker, 2008;Cutler, Lecumberri, & Cooke, 2008;Golestani, Rosen, & Scott, 2009;Lecumberri & Cooke, 2006;Rosenhouse et al, 2006;Shimizu, Makishima, Yoshida, & Yamagishi, 2002). Researchers using babble noise have investigated single-talker babble noise (see, e.g., Brungart, 2001), multi-talker babble noise (as in Simpson & Cooke, 2005), or speech played in reverse (e.g., Moll et al, 2001.…”
Section: Distortion and Noisementioning
confidence: 99%
“…Infants have limited experience with their native language. In this regard, they may be more comparable to second-language learners than to native adult speakers of a language, and several studies suggest that second-language learners have particular difficulties comprehending speech in noise or in the presence of other speech (Cooke, Garcia Lecumberri, & Barker, 2008;Garcia Lecumberri & Cooke, 2006;Mayo, Florentine, & Buus, 1997;Takata & Nábelek, 1990).…”
mentioning
confidence: 99%